Diatoms in a sediment core from a flood pulse wetland in Malaysia record strong responses to human impacts and hydro‐climate over the past 150 years. Issue 1 (13th May 2020) - Briddon, Charlotte L.; McGowan, Suzanne; Metcalfe, Sarah E.; Panizzo, Virginia; Lacey, Jack; Engels, Stefan; Leng, Melanie; Mills, Keely; Shafiq, Muhammad; Idris, Mushrifah
Abstract : Rapid development and climate change in southeast Asia is placing unprecedented pressures on freshwater ecosystems, but long term records of the ecological consequences are rare. Here we examine one basin of Tasik Chini (Malaysia), a UNESCO‐designated flood pulse wetland, where human disturbances (dam installation, iron ore mining, oil palm and rubber cultivation) have escalated since the 1980s. Diatom analysis and organic matter geochemistry (δ 13 Corg and C/N ratios) were applied to a sediment sequence to infer ecological changes in the basin since c. 1900 CE. As the Tasik Chini wetland is a rare ecosystem with an unknown diatom ecology, contemporary diatom habitats (plant surfaces, mud surfaces, rocks, plankton) were sampled from across the lake to help interpret the sedimentary record. Habitat specificity of diatoms was not strongly defined and, although planktonic and benthic groupings were distinctive, there was no difference in assemblages among the benthic habitat surfaces. An increase in the proportion of benthic diatom taxa suggests that a substantial decrease in water level occurred between c. 1938 and 1995 CE, initiated by a decline in rainfall (supported by regional meteorological data), which increased the hydrological isolation of the sub‐basin. Changes in the diatom assemblages were most marked after 1995 CE when the Chini dam was installed. After this time both δ 13 Corg and C/N decreased, suggesting an increase in autochthonous production relative to allochthonous river flood pulse inputs. Oil palm plantations and mining continued to expand after c. 1995 CE and we speculate that inputs of pollutants from these activities may have contributed to the marked ecological change. Together, our work shows that this sub‐basin of Tasik Chini has been particularly sensitive to, and impacted by, a combination of human and climatically induced changes due to its hydrologically isolated position. Abstract : This research examines one basin of Tasik Chini (Malaysia), a UNESCO‐designated flood pulse wetland, where human disturbances (dam installation, iron ore mining, oil palm and rubber cultivation) have escalated since the 1980s. We combine multiple habitat sampling of contemporary diatom assemblages across Tasik Chini with palaeolimnological techniques (diatom, analysis, carbon isotope composition [δ 13 Corg ] measurements, C/N ratios of organic matter and 210 Pb dating) to reconstruct how Tasik Chini has changed over the past c. 150 years. We conclude that this sub‐basin of Tasik Chini has been particularly sensitive to, and impacted by, a combination of human and climatically‐induced changes due to its hydrologically isolated position.